2021
DOI: 10.53223/sinappsi_2021-02-1
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading Italy's Industrial Capacity: Industry 4.0 across Regions and Sectors

Abstract: How are Industry 4.0 investments distributed across Italian regions and sectors? Which are the main drivers of diffusion? To address these questions, in this study we exploit rich firm survey data on the adoption of the new digital technologies and examine their adoption patterns. On the one hand, we produce novel insights into the drivers of structural change in the Italian economy, and on the other, we provide evidence on the technological upgrading of Italy's production capacity that is relevant for policy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…18 On this ground, ISTAT (2018) and MISE ( 2018) propose a detailed discussion on the role of I4.0 fiscal incentives for Italian firms investment plans. Moreover, Cirillo et al (2021) recently provide a descriptive overview on the distribution of such I4.0 incentives among Italian sectors and geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…18 On this ground, ISTAT (2018) and MISE ( 2018) propose a detailed discussion on the role of I4.0 fiscal incentives for Italian firms investment plans. Moreover, Cirillo et al (2021) recently provide a descriptive overview on the distribution of such I4.0 incentives among Italian sectors and geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…More so than robots. This is corroborated by evidence about the geographical spread of this technology, which is well-represented in all Italian macro-regions precisely because of its broader, not narrower, 'enabling' potential (Cirillo et al, 2022a). 20 In the Appendix we provide a further exercise splitting the sample in manufacturing and construction versus services (see Table A6).…”
Section: Discussionmentioning
confidence: 69%
“…In the study of technical change, several factors have been identified as drivers of technology adoption choices, and much has been written on how these choices translate into aggregate patterns of technology diffusion (for comprehensive reviews of this literature, see Karshenas and Stoneman, 1993;Hall and Khan, 2003;Stoneman and Battisti, 2010). 2 among the drivers of adoption, we can distinguish between: i) supply-side factors, including improvements of older technologies leading to incremental innovations or changes in the use of existing technologies (Gruber and Verboven, 2001); ii) factors related to the demand for new technologies, such as technological complementarities between producers and users, and the adopters' stock of tangible and intangible capital (Rosenberg, 1976); iii) specific (internal) characteristics of the firm, such as size, 3 age, and human resource management practices (Bloom et al, 2012); iv) sectoral heterogeneities between manufacturing and services (Comin and Mestieri, 2013;Calvino et al, 2018;Cirillo et al, 2022a); and finally v) the external organisation of the firm and the institutional context in which businesses operate (Dosi, 1991;Mowery and Rosenberg, 1993). More broadly, the co-evolution of 1 The few works that address this issue include Calvino et al (2022) inspecting the role of workers' skills as well as management capabilities, and accumulation of intangible assets as main drivers of digital technologies in the Italian economy.…”
Section: Background Literature and Hypothesesmentioning
confidence: 99%